Orthodontics at Times of National Emergency: Past and Current Crises Part 1: Past Crises and Lessons Learnt. (2nd July 2020) - Lee, Tara V N; Fowler, Peter V; Williams, Julie C; Ellis, Pamela; Atack, Nikki E; Ireland, Anthony J
Abstract : This paper explores past natural disasters such as Hurricane Katrina (USA), the Great East Japan and Christchurch (New Zealand) Earthquakes as well as the HIV and SARS pandemics and the impact they had on providing orthodontic services at the time of the crisis. It also addresses the lessons learnt during the process of recovery and the long-term changes made as a result to the provision of care. CPD/Clinical Relevance: To provide a review of how orthodontics as a specialty survived past crises and to use the lessons learnt to navigate the current COVID-19 pandemic.